2016
DOI: 10.1186/s40463-016-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Mental practice in postgraduate training: A randomized controlled trial in mastoidectomy skills

Abstract: BackgroundMental practice, the cognitive rehearsal of a task in the absence of overt physical movement, has been successfully used in teaching complex psychomotor tasks including sports and music, and recently, surgical skills.The objectives of this study were, 1) To develop and evaluate a mental practice protocol for mastoidectomy 2) To assess the immediate impact of mental practice on a mastoidectomy surgical task among senior Otolaryngology─Head & Neck Surgery (OHNS) residents.MethodThree expert surgeons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Differences in the handling of instruments might be caused by differences in mental practice. Mental practice utilizes the systemic use of mental imagery to rehearse an action before the actual performance without the need for physical movement [ 27 , 28 ]. Mental practice has been validated as an efficient training method in teaching laparoscopic surgery [ 27 ], as well as in learning basic surgical skills [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the handling of instruments might be caused by differences in mental practice. Mental practice utilizes the systemic use of mental imagery to rehearse an action before the actual performance without the need for physical movement [ 27 , 28 ]. Mental practice has been validated as an efficient training method in teaching laparoscopic surgery [ 27 ], as well as in learning basic surgical skills [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mental practice has been successfully implemented in teaching and rehearsing complex psychomotor tasks in several domains such as sports or music [ 28 ]. Our data indicated that sports activity positively correlates with operative performance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the beginner showed a tendency to omit key points, thus decreasing mental representation duration. [27] During the third session, actual practice duration decreased due to skill execution improvement while that of MI increased, thus attesting that the exp group took into account most elements of the script and that the quality of mental representation improved. This resulted in better congruence between actual and imagined execution times, close to isochrony, thus confirming that both tasks share similar processes.…”
Section: Resultsmentioning
confidence: 86%
“…The exp group performed significantly better than the ctrl group from the second training session showing that MI is quickly effective. During initial learning where a high volume of knowledge was to be learnt, [27] MI better concretized the operations to be carried out and made possible to segment them into several sub-objectives. The association of MI with real practice led to better efficiency than in the ctrl group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation